2023
DOI: 10.1002/csr.2582
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and dividend payout policy in extraordinary time: Empirical study of South Africa

Abstract: Corporate social responsibility (CSR) is a strategic tool that firms use to gain competitive advantage and enhance profitability in the long run, yet its effect on dividend payout in extraordinary times is limited. Grounded in stakeholder and dual responsibility theories, this study examines the effect of CSR on the relationship between COVID‐19 and dividend payout. Data from the period 2015–2021 were obtained from 114 non‐financial listed firms on the Johannesburg Stock Exchange, South Africa, and analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Almeida et al (2020) also highlighted that there is a connection between the social performance and dividend policy of the organizations. Buertey, Ramsawak, et al (2024) concluded that firms should focus on their social goals to attract the shareholders for reasonable dividend policy.Based on this discussion, the following hypothesis is developed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Almeida et al (2020) also highlighted that there is a connection between the social performance and dividend policy of the organizations. Buertey, Ramsawak, et al (2024) concluded that firms should focus on their social goals to attract the shareholders for reasonable dividend policy.Based on this discussion, the following hypothesis is developed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following the works of Buertey et al (2023) and Poursoleyman et al (2023), COVID-19 is captured as a dummy variable of one (1) for the years 2020 and 2021, and zero (0) otherwise. This is because COVID-19 related restrictions went into effect in South Africa in 2020 and by the end of 2021 many restrictions on movement and social activities had been removed both in South Africa and in many countries globally and life had returned to almost normalcy.…”
Section: Main Research Variables and Measurementmentioning
confidence: 99%
“…The ratings from the four categories are subsequently used to calculate the overall performance score for a firm monthly. Following the examples of Thompson et al (2022) and Buertey et al (2023), we combined the monthly CSR performance ratings of the sampled firms to produce an equally weighted annual average rating for each firm. Given its wide data sources and proprietary methods of data processing, the CSRHub database has become a trusted global data source on firm CSR performance, widely used by professionals from industry, research, and academic institutions.…”
Section: Main Research Variables and Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Firm Size ControlThe natural logarithm of a company's total assets(Singh and Kumar 2017;Moradi et al 2021;Akbar et al 2021;Tarkom 2022;Zimon et al 2024).Firm Age ControlThe number of years of company activity(Singh and Kumar 2017;Le 2019;Akbar et al 2021;Hashmi and Iqbal 2022; Naz et al 2022;Almustafa et al 2023).Sale Growth ControlIt is the rate of change in sales from the previous year to the current year(Singh and Kumar 2017;Akbar et al 2021;Tarkom 2022; Naz et al 2022).Tobin Q ControlThe ratio of Tobin Q equals to the market value of equity to book value of total assets(Akbar et al 2021;Tarkom 2022;Ahmad et al 2022).Tangibility ControlTangibility shows the ratio of property, plant, and equipment to total assets(Singh and Kumar 2017;Tarkom 2022).Dividends ControlDividends represent the payments a firm makes to its shareholders as a return on the company's profits(Le 2019;Buertey et al 2024;Al-Hiyari et al 2024).∆GDP ControlIt is equal to the current year's gross domestic product (GDP) minus the previous year's GDP divided by the previous year's GDP(Nazir and Afza 2009;Akbar et al 2021;Moradi et al 2021;Ahmad et al 2022;Angosto-Fernández and Ferrández-Serrano 2024).…”
mentioning
confidence: 99%